The Treatment Action Campaign (TAC) case as a model for the protection of the right to health in Africa, with particular reference to South Africa and Cameroon - Atangcho, A.N. (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2005.